Fabrication and magnetic properties of P2O5-CaO- Na2O bioactive glass ceramic containing BaFe 12O 19 - Pratthana Intawin (2018)
The fabrication of bioactive glass ceramics containing BaFe1 2 O 19 (BF) crystals has been carried out for the application in hyperthermia treatment. The BaFe1 2 O 19 powder was firstly prepared and subsequently mixed with the non-silicate P 2 O 5 -CaO-Na 2 O bioactive glass with various BF concentrations. After that, the glass ceramics were produced via a sintering method at 600°C and their crystal phases were examined by XRD and in vitro test was carried out by soaking in simulated body fluid. Remanence and saturation magnetization and coercivity were deduced from magnetic measurement. It was found that the samples exhibited magnetic behavior which is similar to hard magnetic materials. © 2013 Copyright Taylor and Francis Group, LLC.